Design and Fabrication of MEMS Heatuator for Automotive Device Applications - Zaliman, Sauli, Prof. Madya; Hasnizah, Aris; Razaidi, Hussin; Mohd Hafiz, Ismail; Rizalafande, Che Ismail (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Madya Zaliman Sauli and his team from School of Microelectronic Engineering won gold for Design and Fabrication of MEMS Heatuator for Automotive Device Applications.